Medullary bone in an Early Cretaceous enantiornithine bird and discussion regarding its identification in fossils. Issue 1 (December 2018) - O'Connor, Jingmai; Erickson, Gregory; Norell, Mark; Bailleul, Alida; Hu, Han; Zhou, Zhonghe
Abstract Medullary bone is an ephemeral type of bone tissue, today found only in sexually mature female birds, that provides a calcium reservoir for eggshell formation. The presence of medullary bone-like tissues in extant birds, pterosaurs, and dinosaurs distantly related to birds shows that caution must be exercised before concluding that fossils bear medullary bone. Here we describe a new specimen of pengornithid enantiornithine from the Lower Cretaceous Jiufotang Formation. Consisting of an isolated left hindlimb, the three-dimensional preservation contrasts with the crushed preservation characteristic of most Jehol specimens. Histological examinations suggest this resulted from the presence of a thick layer of highly vascular bone spanning the medullary cavities of the femur and tibiotarsus, consistent with expectations for medullary bone in extant birds. Micro-computed tomographic scans reveal small amounts of the same tissue extending into the pedal phalanges. We consider the tissue to be homologous to the medullary bone of Neornithines. Medullary bone is used by modern female birds as a calcium reservoir for eggshell production. Here, O'Connor and colleagues propose criteria for identifying medullary bone in fossils and report medullary bone from a Cretaceous enantiornithine bird fossil.